Co-pyrolysis of corn stalk and coal fly ash: A case study on catalytic pyrolysis behavior, bio-oil yield and its characteristics. (October 2022) - Hong, Wenpeng; Zhang, Yu; Jiang, Haifeng; Li, Shu; Chen, Jie; Zhang, Ling
Abstract: In this paper, industrial solid waste coal fly ash and agricultural solid waste corn stalk were used as the research object. The aim is to realize the comprehensive utilization of solid waste and obtain high-quality bio-oil. Thus, the effects of pyrolysis conditions on the pyrolysis process were discussed, and the catalytic effects of coal fly ash were explored using the TGA, SEM-EDS, XRD, FTIR, and GC-MS. The results of TGA coupled with the Coats-Redfern model indicate that the total apparent activation energy varied from 408.40 kJ/mol to 387.39 kJ/mol and co-pyrolysis is a endothermic process while the initial pyrolysis temperature(Ti ) is advanced after adding coal fly ash. The highest yield of bio-oil is 30.06 ± 0.03 wt%. It is obtained at 500 °C with a 50% mass fraction of coal fly ash. Additionally, ketonization reactions are promoted, leading to the content of ketones in bio-oil increased by about 10.28%. The selectivity of hydrocarbons is also improved, especially, aliphatic hydrocarbons increase by about 7.89%. The reasons are deeply analyzed and discussed. Overall, the results demonstrate that the participation of coal fly ash not only improves the pyrolysis behavior of biomass but also promotes the enrichment of ketone chemicals in the bio-oil.